Growth‐Stage‐Based Irrigation Management on Biomass, Yield, and Yield Attributes of Spring Canola in the Southern Great Plains. Issue 6 (30th August 2018) - Katuwal, Krishna B.; Angadi, Sangamesh V.; Singh, Sukhbir; Cho, Youngkoo; Begna, Sultan; Umesh, M. R.
Abstract : Extensive use of groundwater for irrigation has significantly depleted the Ogallala aquifer, threatening the sustainability of irrigated agriculture in the Southern Great Plains. There is a need to identify a low‐water‐requiring alternative crop and understand the response of that crop to deficit irrigation strategies. The objective of this study was to assess biomass partitioning and yield of spring canola ( Brassica napus L.) under deficit irrigation. Three diverse canola cultivars ('H930', 'H955', and 'L140') were grown under four different irrigation treatments; full season irrigation (FI), no irrigation at the vegetative stage (VS), no irrigation at the reproductive stage (RS) and dryland (DL) at Clovis, NM, on Olton clay loam soil. Seed yield of VS was similar to FI in both years but was greater by 93 and 200% in 2015 and by 120 and 263% in 2016 than RS and DL, respectively. Biomass and oil yield of VS were similar to those of FI in 2015 but were lower by 14% in 2016. Relieving water stress with irrigation at flowering increased leaf area index of VS and made it similar to that of FI by pod development stage. Biomass accumulation was greater in treatments receiving irrigation after flowering and most of the post‐flowering biomass was partitioned into reproductive parts. Among yield components, greater 1000‐seed weight in VS than RS and DL, indicated recovery of canola stressed at the vegetative stage. Results indicated that if water is limited, the vegetative growth stage would be a better time to skip irrigation in spring canola.